European Jewry in the Age of Mercantilism, 1550-1750. - Israel, Jonathan I. (Littman Library of Jewish Civilization, The, 1997)
The first edition of this book was the joint winner of the Wolfson Literary Prize for History in 1986. For this third edition, the book has been updated and includes a new introduction.